2005
DOI: 10.1002/glia.20164
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated cerebral ischemic injury by activated macrophages/microglia after lipopolysaccharide microinjection into rat corpus callosum

Abstract: In cerebral ischemic insults, activated inflammatory cells such as microglia and macrophages may be implicated in the pattern and degree of ischemic injury by producing various bioactive mediators. In the present study, we provide the evidence that activated microglia/macrophages accelerate cerebral ischemic injury by overexpression of inducible nitric oxide synthase (iNOS). To activate microglia/macrophages, a potent inflammation inducer lipopolysaccharide (LPS, 5 microg/5 microl) was microinjected into rat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 55 publications
5
48
1
Order By: Relevance
“…1, 45 We also found that LPS-activated microglia and monocytes accelerated and aggravated cerebral ischemic injury, 34 and that depletion of peripheral leukocytes by ␥-irradiation before ischemia reduced the cerebral infarction caused by MCAO/R (unpublished data). In the present study, LJ529 was found to inhibit the infiltration/migration of microglia/monocytes induced by MCAO/ R or injection of LPS into the corpus callosum ( Figure 1).…”
Section: Discussionmentioning
confidence: 73%
“…1, 45 We also found that LPS-activated microglia and monocytes accelerated and aggravated cerebral ischemic injury, 34 and that depletion of peripheral leukocytes by ␥-irradiation before ischemia reduced the cerebral infarction caused by MCAO/R (unpublished data). In the present study, LJ529 was found to inhibit the infiltration/migration of microglia/monocytes induced by MCAO/ R or injection of LPS into the corpus callosum ( Figure 1).…”
Section: Discussionmentioning
confidence: 73%
“…Because nitrogen species contribute to responses in inflamed brain (Brown and Bal-Price, 2003;Lee et al, 2005), we examined levels of inducible enzyme iNOS and 3-NT. Marked upregulation of iNOS was evident in LPS-injected striatum (at 24 h) with colocalization to microglia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…26 These cells are a source of cytokines and other inflammatory mediators 34 and, when activated after a cerebral ischemia, accelerate injury via an overexpression of inducible nitric oxide synthase and production of cytotoxic nitric oxide. 27 In accordance with the similar levels of hippocampal cytokines between the groups, we also saw similar levels of activated microglia.…”
Section: Discussionmentioning
confidence: 99%